Geomechanical Integrity Assessment in Field X of the Telisa Formation Caprock for CO₂ Storage in the Central Sumatra Basin - Abdillah, Hanif Ridho; Aurell Alyya Charissa; Handoyo Handoyo; Samosir, Sondang (Universitas Islam Negeri Ar-Raniry, 2026)
Evaluating caprock integrity is essential to ensure the long-term security of geological CO₂ storage. This study assesses the elastic and geomechanical characteristics of the Telisa Formation in the Central Sumatra Basin as a potential caprock for Carbon Capture and Storage (CCS). The analysis integrates well log data from four wells (C-1, H-1, P-1, and T-1), including gamma ray, sonic, density, and predicted shear-wave velocity logs. Elastic parameters such as Young’s Modulus (1–15 GPa) and Poisson’s Ratio (0.3–0.5) were calculated and used to derive the Brittleness Index (0–1.5), while Unconfined Compressive Strength (35–65 MPa) was estimated to evaluate rock strength. The results indicate that the Telisa Formation is predominantly shale-dominated, characterized by high gamma ray values and low porosity, consistent with typical caprock properties. Acoustic Impedance, Young’s Modulus, and UCS generally increase with depth, reflecting progressive compaction and enhanced rock stiffness. Crossplot analyses reveal positive correlations between Acoustic Impedance, Young’s Modulus, Brittleness Index, and UCS, and a negative relationship between Poisson’s Ratio and stiffness-related parameters. Although localized less brittle-to-brittle intervals are identified, particularly in Well P-1, the formation overall exhibits ductile to less brittle behavior. These findings suggest that the Telisa Formation demonstrates favorable mechanical integrity for CO₂ containment, if injection pressures are carefully managed and structural discontinuities are properly evaluated to minimize leakage risk.